Pengembangan Perangkat Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions (STAD) pada Materi Persamaan Kuadrat di Kelas X SMA - Hasia Marto (Paedagogik, 2013)
The character of the nation is currently experiencing a severe fragility. Various people rate as a result of the imbalance of purpose in educational practice in schools. The purpose of learning is not oriented of cultivation of characters, but more cognitively oriented. This study aimed to develop science learning model integrated with character value (Model PIN-Karakter) in elementary school are valid, practical, effective and attractive to conceive a character value and improve science learning outcomes. The metodology used in this research is Research and Development (R & D). The research subject is elementary school's student's and teachers in grade 4, in Makassar South Sulawesi. This research is the development of plot development using Plomp, by taking five phases, namely: (1) investigation, (2) design, (3) realization, (4) validation testing. and revision, and (5) implementation. The metodology used in this research is Research and Development (R & D). The research subject is elementary school's student's and teachers in grade 4, in Makassar South Sulawesi. Data collection is using validation sheet, observation, test learning outcomes, and questionnaires, supported by logbook. The data is analysed by descriptive quantitative and qualitative- The results indicate that the development of. (1) Model PIN-Karakter comply criteria validity, practicality, effectiveness and attractiveness, and (2) the process of cultivation character value take place in stages and hierarchical follow of syntax Model PIN-Karakter, with two patterns of integration, the integration content-based and integration activity-based. Syntax of Model PIN-Kayakter consists of six phases, namely: (i) conditioning concepts and values, (ii) the organization of the group, (iii) the value of exploration and growth, (iv) explanation and deepening of value, (v) application and commitment to value; and (vi) evaluation and habituation value. Kata Kunci: model pembelajaran IPA, integrasi nilai karakter, sekolah dasar